Mental and behavioral disorders due to substances during the COVID-19 Pandemic: Prevalence, diagnosis, and management - Era Catur Prasetya; Kharisma Sukma Nanda; Khofifah Dwi Oktaviana; Lens Hanin Herda Zhafirah; Lia Lisa Arista; M Dedi Dermawan (Universitas Muhammadiyah Surabaya, 2022)
ABSTRACT COVID-19 (Coronavirus Disease 2019) is still a significant problem; therefore, mental health issues and COVID-19 are starting to get attention because of the increasing psychological impact and mainly because of Substance Use Disorder (SUD). Further study is required on this issue. This paper aimed to determine the prevalence, diagnosis, and treatment of SUD during the COVID-19 pandemic. This literature review is gained from scientific articles with a range of publication years from 2016 to 2021 about SUD During the COVID-19 pandemic based on Prevalence, Diagnosis, and psychotherapy of the published journal using Pubmed, Google Scholar, and SAGE Journals, and then critically reviewed. The prevalence of SUD patients during the COVID-19 pandemic has increased; however, digital psychotherapy strategies for SUD patients have been found and proved effective during the pandemic. In conclusion, the COVID-19 pandemic impacts a person's mental and behavior and could be a high-risk opportunity for substance abuse. Therefore health workers must improve health services for SUD patients to receive the health access needed even in a pandemic.Keywords: Mental Health, Substance Use Disorder, COVID-19, Prevalence, Diagnosis, ManagementCorrespondence : dedydermawan555@gmail.com